Evaluation of the effectiveness of parameters of the global description of words in simple automatic speech recognition systems - Cz. BASZTURA; W. MAJEWSKI; W. BARYCKI (Archives of Acoustics)
In this paper, oriented at the so-called simple systems of speech recognition, the effectiveness of 6 sets of parameters in the global description of words in a given vocabulary was analysed. The usability of simple parametrization methods and such parameters as: density of zero-crossings, distribution of intervals between zero-crossings, parameters of two so-called phase planes, spectral parameters in octave and tertiary bands, was investigated and analysed on the basis of sound material for one operator, mainly and a vocabulary from 5 to 40 words. It was proved that such parameters as the density of zero-crossings and the distribution of time intervals between zero-crossings can be applied in simple systems with a vocabulary preferably not exceeding 10 words, unless it would be possible to select certain words from the vocabulary. Parameters of the first phase plane and spectral parameters exhibited positively weak discrimination ability, especially in octave bands. Also the usability of the NN algorithm and the Camberra distance which standarizes parameters in such ASR systems was confirmed.